Tempo e espaço : a gramaticalização do item onde em textos religiosos (Séculos XIV, XVI e XXI) - Souza, Adriana dos Santos (2007)
This research aims to observe the linguistic change which the item where passes through, when assuming values not announced by the traditional grammar and that are, however, frequently registered either in oral or writing practice. Among these "ab-uses" of the particle, we investigate the one that indicates time, along several texts, oral and written, of religious thematic, produced in the 14th, 16th and 21st centuries to confirm that this usage didn't show up as a linguistic innovation of the current Portuguese speaker, but it's understood as a changing process. The analysis is developed on studies about grammaticalization, since there is a large range of literature about the phenomenon and also contemplates discussions concerning the adverbs, class in which, etymologically, the researched element is inserted. We also treat some points referring to the Catholic Church, the marks of the religious speech and the expression of time based on the concept of space. We have researched, in a parallel with the temporal sense, cases of locative anaphors of the element, highlighting the possibility of variation between it and a prepositioned syntagm, when geographical entities are retaken. By the end we confronted the data which were a result of the three synchronies and showed clues of the grammaticalization process the where has been suffering diachronically.